Stress Management in School Teacher: Implications for Da'wah - Isa, Yakubu (Darul Yasin Al Sys, 2024)
Stress is an uneasy situation challenging the academic staff worldwide. However, many of the school teachers are unable to properly manage the temptations and effects of stress. It is notable that millions of school teachers are suffering from stress, huge money is being spent for caring for stress patients from the academic cycle all in the name of stress. Albeit, stress occur due to external (home or society based factors), internal (school) factors such as classroom disruption, poor infrastructure (teaching aids), poor personality of teachers or students, poor working conditions, etc. Teachers should be provided with adequate support and conducive teaching environment. Teachers shall improvise ways to curtail stress by engaging in prayers, leave, sabbatical, capacity building, healthy eating, physical activities, etc. More importantly, the role of religious interventions could be overstated in tackling stress. Religious communication can use prayers (in all its forms), reading the Qur’an, empowerment, and other religious da’wah methods to surmount stress.